Design behaviour and distributed cognition: a protocol study on the effect of design tools on the process of architectural design thinking - Tahsiri, Mina (2018)
This thesis, is an explorative research, manifesting factors that influence the relationship between a designer and their design tool. The interest of the thesis is in the epistemic role of a design tool and how it can influence a designer’s thinking in the concept development phase of architectural design. A diversity of views regarding the effect of design tools on design thinking led the thesis to propose a new protocol think-aloud study framework for studying design behaviour based on the theory of Distributed Cognition, where cognition is seen to be distributed between the internal space of the mind and the external space provided by the medium of the design tool.